If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5m + -35 = 6m + 60 Reorder the terms: -35 + 5m = 6m + 60 Reorder the terms: -35 + 5m = 60 + 6m Solving -35 + 5m = 60 + 6m Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-6m' to each side of the equation. -35 + 5m + -6m = 60 + 6m + -6m Combine like terms: 5m + -6m = -1m -35 + -1m = 60 + 6m + -6m Combine like terms: 6m + -6m = 0 -35 + -1m = 60 + 0 -35 + -1m = 60 Add '35' to each side of the equation. -35 + 35 + -1m = 60 + 35 Combine like terms: -35 + 35 = 0 0 + -1m = 60 + 35 -1m = 60 + 35 Combine like terms: 60 + 35 = 95 -1m = 95 Divide each side by '-1'. m = -95 Simplifying m = -95
| 45-7x+2x=100 | | 15-2x=8x-25 | | 8m+40=4m+4 | | X-5+6-2x=3x-4-x-1 | | 3-3=-7 | | 2squared+x=50 | | 3(x-2)=2(3x+4) | | 9p+9=2p-10 | | -2x+12=-17x+72 | | 3x+6=6x-60 | | 26+x=-4x | | 5x+15=6x-18 | | 7k-70=4K-12 | | -7x-6(x+6)=-101 | | B=-b+4+(3b-2)-(8b-5a) | | 48+x=50 | | -42-4y=-26 | | 7x+7=2x-16 | | 7m-21=5m+5 | | 4y+ax=b+8yforx | | -7x-6(x+6)=101 | | 13-14b=14-1-4b | | X+50y-140000=0 | | 3n-18=7n+28 | | 4y+2x-y= | | 2.5x-2.4=22.6 | | 12x-14x= | | 4n-40=2n | | x^2-4y+2x+5=0 | | 10x-30=12+5x | | 10ab^2-15abc+5a^3bc=0 | | -3n+6=5n |